2021
DOI: 10.1126/science.abj7364
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine nationalism and the dynamics and control of SARS-CoV-2

Abstract: Vaccines provide powerful tools to mitigate the enormous public health and economic costs that the ongoing SARS-CoV-2 pandemic continues to exert globally, yet vaccine distribution remains unequal among countries. To examine the potential epidemiological and evolutionary impacts of ‘vaccine nationalism’, we extend previous models to include simple scenarios of stockpiling between two regions. In general, when vaccines are widely available and the immunity they confer is robust, sharing doses minimizes total ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 68 publications
0
81
0
1
Order By: Relevance
“… 2-4 Several vaccines that are highly effective in reducing the incidence of hospitalization and death have been authorized; however, vaccine coverage remains insufficient. 5 , 6 Antiviral therapies that reduce the risk of Covid-19 progression are needed. Since trials have shown the need for initiation of treatment as soon as possible after the onset of symptoms, 7-9 such therapies would ideally be readily available and easily administered by the patients themselves.…”
mentioning
confidence: 99%
“… 2-4 Several vaccines that are highly effective in reducing the incidence of hospitalization and death have been authorized; however, vaccine coverage remains insufficient. 5 , 6 Antiviral therapies that reduce the risk of Covid-19 progression are needed. Since trials have shown the need for initiation of treatment as soon as possible after the onset of symptoms, 7-9 such therapies would ideally be readily available and easily administered by the patients themselves.…”
mentioning
confidence: 99%
“…However, this strategy only works in countries with access to ample vaccine supplies and the ability to administer multiple doses of complex vaccines over time. Without a major investment in equitable global mass vaccination, we cannot exclude the likelihood of significant future evolution of transmissive and immunologically elusive new variants 7 .…”
Section: Impact Of Transmission Heterogeneitiesmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, inequities in global vaccine distribution 2 , as well as vaccine hesitancy 3 are significant brakes on vaccination rates at different scales. Second, the impact of the vaccine may be reduced by biological factors, notably immunological complexities [4][5][6][7] and viral evolution [6][7][8][9] . We can illustrate these forces by reference to the simplest, most optimistic case where vaccination and natural infection provide lifelong immunity against reinfection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), on the trajectory of the epidemic 3,510 . More recently, models have explored a wide range of biological and behavioural aspects of COVID-19 vaccination programmes, including vaccine efficacy, emerging variants, social determinants of vaccine access and uptake, waning immunity, and changes in behaviour due to vaccination impact 1115 . Models have elucidated important epidemiological transmission parameters, and have produced short-term projections of cases, hospitalizations, and deaths that can be expected in different populations 1619 .…”
Section: Introductionmentioning
confidence: 99%